Rancang Bangun Ekonomi Pendidikan dalam Investasi Pendidikan Islam - Arwani, Agus (Madaniyah, 2017)
Training leads to the productivity of educated labor. Nevertheless, how the big contribution to growth is still the unanswered question accurately. Hence, it is also strange how the comparison between the level of Economics Behind The results of educational investments compared with investments in other sectors. Schooling is the social institution needed to produce educational products and services. Educational outcomes can be categories as consumption and investment.. As consumption, the results are immediately and directly enjoyable, called âoutputsâ. While as investment, education give benefits indirectly and in the long term continuity, named âoutcomesâ. Also the results can be differentiated as economic valued outputs and non-economic valued outputs. The first one is outputs which potentially useful to get financial or monetary advantages, as knowledge and skills. While the second one is benefits which cannot be measured as money, like friendship, happiness, etc. The calculation of economical education results carried out by formulas: the earnings differentials, net present value, or internal rate of return, etc. This computation is very important to make a decision or consideration in choosing and continue studying, to explain manpower condition, and to improve education program to meet with manpower demand.